PEDAGOGICAL-PSYCHOLOGICAL ASPECTS OF THE USE OF MASS MEDIA FOR THE FORMATION OF SOCIAL CONSCIOUSNESS IN PRESCHOOL CHILDREN - Nazirova Guzal Malikovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In article influence of media environment on formation of social experience of children of preschool age is analyzed. Positive and negative sides of media education of preschool children are lit. The role of parents and teachers in the course of formation of social experience under the influence of media environment is characterized. Councils for improvement of positive impact of a media environment on formation of social experience of preschool children are offered.